Thai society for metabolic and bariatric surgery consensus guideline on bariatric surgery for the treatment of obese patient in Thailand - A. Techagumpuch (2020)
© Journal of the Medical Association of Thailand. Background: The prevalence of obesity is increasing in Thailand. The Thai Society for Metabolic and Bariatric Surgery just developed the first Thailand guideline for Bariatric surgery as a gold standard treatment of morbid obesity. Objective: To enhance the quality of care in obesity treatment through metabolic and bariatric surgery Methods: The present study would provide suggestions for management that were derived from available knowledge, peer-reviewed of scientific literature, and expert opinion. The guideline was developed by performing a review of currently available literatures regarding obesity, obesity treatments, and metabolic surgery from all references published worldwide. Results: The intent of issuing such a guideline is to provide definite criteria for surgery, pre-operative care, and post-operative care, including practical points in each step. Conclusion: This is the first practice guideline on bariatric surgery for the treatment of obese patient in Thailand. The guideline would be revised in the future should additional evidence become available and future research is needed to gather more evidence and study clinical outcomes for the development of future practice guidelines.